[Logging in Palawan ; Game of the generals ; Nonoy Marcelo [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
Tackles logging activities of alledged businessman in Palawan; controversy between Gen. Alfredo Lim and Gen. Almonte regarding the intervention of the WPD in a smuggling bust by EIIB; and the philosophy and creative talent of the creator of "Tisoy", Bubwit and cartoon characters that comment on political events in the Philippines.